2022
DOI: 10.1111/odi.14319
|View full text |Cite
|
Sign up to set email alerts
|

Significance of chlorine‐dioxide‐based oral rinses in preventing SARS‐CoV‐2 cell entry

Abstract: Objective This work aims to determine the efficacy of preprocedural oral rinsing with chlorine dioxide solutions to minimize the risk of coronavirus disease 2019 (COVID‐19) transmission during high‐risk dental procedures. Methods The antiviral activity of chlorine‐dioxide‐based oral rinse (OR) solutions was tested by pre‐incubating with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) pseudovirus in a dosage‐dependent manner before transducing to human embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Out of these, three clinical studies were eligible for quantitative analysis [27] , [28] , [29] . The reasons for exclusion after full-text screening are reported in Table 3 [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of these, three clinical studies were eligible for quantitative analysis [27] , [28] , [29] . The reasons for exclusion after full-text screening are reported in Table 3 [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] .…”
Section: Resultsmentioning
confidence: 99%
“… Nasal spray(s) alone or in combination with mouthwash(es) 8 [30] , [31] , [33] , [34] , [40] , [41] , [59] , [64] 2. Study type (in silico, animal studies, case report/series, non-randomized clinical trials, review, no experimental data) 14 [42] , [46] , [47] , [48] , [54] , [60] , [62] , [63] , [68] , [71] , [82] , [85] , [86] , [125] 3. Off-topic 4 [32] , [35] , [45] , [49] 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of interaction with dental materials, HOCl has been found to increase the bond strength between the tooth and self‐adhesive resin cement (Totaro et al, 2022). In terms of biocompatibility, HOCl is an agent with antimicrobial activity, which is naturally produced by the human immune system to fight infection (Zoni et al, 2007) and has been reported to show similar antibacterial activity to NaOCl on E. faecalis , but much lower toxicity than NaOCl (Travis et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we were interested in testing the effect of plant cell-engineered gold nanoparticles (pAuNPs) in the presence or absence of conjugated quercetin on SARS-CoV-2 and HSV-1 viruses as they pose a significant risk, specifically in dental clinic settings and procedures with no commercial antiviral drugs available to target the entry of pathogenic variants of SARS-CoV-2 or with the emerging drug-resistant strains of HSV-1 [16][17][18]. Interestingly, our group reported the development of plant-engineered gold nanoparticles (pAuNPs) [19] conjugated with the phytochemical quercetin [personal communication].…”
Section: Introductionmentioning
confidence: 99%